Faktor-Faktor yang Memengaruhi Sikap Mahasiswa terhadap Profesi Akuntansi: Pendekatan Studi Kasus - Renya Rosari; Angela Merici Minggu; Erny Selfina N. Hambandima (Politeknik Ganesha Medan, 2023)
The popularity of the accounting profession in several countries shows concern caused by the declining number of students majoring in accounting which has a direct impact on the supply of accounting graduates for the profession. Therefore, this study aims to find out the factors that influence the attitude of students majoring in accounting towards the accounting profession. This research also explores the interest of students majoring in accounting towards the accounting profession. This study uses a qualitative method with a case study approach. Data was collected through in-depth interviews. Next, the researcher conducts data analysis starting from processing and preparing the data, carrying out the coding process up to interpreting the data. The results showed that the factors driving students' interest in the accounting profession were educational background, accounting learning experience, lecturer teaching methods, interest in accounting, and students' ability to understand the basic concepts of accounting and the accounting profession. This study also found that students majoring in accounting do not absolutely choose an interest in the accounting profession, but they also have an interest in career choices outside the accounting profession.